ChemInform Abstract: 4‐Hydroxyphenylpyruvate Dioxygenase Inhibitors in Combination with Safeners: Solutions for Modern and Sustainable Agriculture. Issue 48 (26th November 2013) - Ahrens, Hartmut; Lange, Gudrun; Mueller, Thomas; Rosinger, Chris; Willms, Lothar; van Almsick, Andreas
Abstract Review: 42 refs.